Peningkatan Kualifikasi Guru IPA dalam Penyusunan LKPD Berbasis Project Based Learning - Coryna Oktaviani; Nurmasyitah Nurmasyitah; Muhammad Reza (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Since the Government launched the prototype curriculum in 2022, the need for integration of project-based learning models into student worksheets (LKPD) has become very important. In fact, there are still many science teachers in Langsa City who do not use LKPD, especially LKPD based on PjBL (Project based learning). Therefore, the purpose of this service is to provide training and assistance in the preparation of PjBL-based LKPD. The method used is the presentation method and guided exercises in the form of mentoring during the practice of preparing PjBL-based LKPD. At the training stage, participants are provided with 16 meeting hours (JP) of materials related to the concept of PjBL-based LKPD, patterns and standards for the preparation of PjBL-based LKPD. Then in the mentoring stage, the teacher is guided by a service team for 16 meeting hours to compile PjBL-based LKPD, which is guided by aspects of appearance, content, and presentation as well as objectives and conclusions. The results of the design were evaluated jointly through a question and answer response after the results of each group's work were presented.